Corpus-assisted discourse analysis of online news on coastal plastic pollution in Kerala / Gokul Jayakumar - Gokul , Jayakumar (2024)
The present study examined the news media portrayal of coastal plastic pollution in Kerala, a Southwestern Indian state that has made the headlines for its poor crisis management. Increasing rates at which plastic-filled garbage has swamped Kerala’s coasts account for a severe plastic waste crisis that affects the livelihoods of its marine and terrestrial lives. Such situations were attributed to a lack of ecological intelligence in Kerala, the most literate state in India, which is vital to realize the importance of nature conservation. Many of Kerala’s urban and large peri-urban populace, which includes high school and college students, read English-language newspapers. Newspapers likely influence their readers, and newspaper readership for young Keralites will enhance their ability in future problem-solving. Newspaper articles are an important source of information for intellectuals and laymen alike. It is also known that many studies in ecolinguistics have used newspaper reports as primary data for their analysis. Thus, this research provides insight into how Kerala’s coastal plastic pollution has been constructed in the online articles of India’s most widely-read English newspaper, The Times of India. A corpus-assisted discourse analytic approach was employed to identify salient language patterns and investigate social actors’ roles in the news reports on this issue based on Theo van Leeuwen’s social actor approach. The analysis revealed the issue has been portrayed as plastic pollution along the coastline, including references to the effects of microplastics and coastal ecology. Further examination demonstrated inadequate news coverage on the roles of social actors, while exclusion strategies of individual actors were significantly observed over collective groupings. Researchers highlighted a lack of a corpus-assisted approach to analyze environmental news discourses in Kerala. This study adds to the genre for discourse analysts who investigate news media portrayals.